Adherence to long-term use of renin-angiotensin II-aldosterone system inhibitors in children with chronic kidney disease - Chien-Ning Hsu; Shiou-Huei Huang; You-Lin Tain (BMC, 2019)
Abstract Background Although renin-angiotensin II-aldosterone system inhibitor (RASI) use for renal protection is well-documented, adherence to RASI therapy in the pediatric population is unclear. This study aimed to evaluate patient characteristics associated with adherence to chronic RASI use in patients with childhood chronic kidney disease (CKD). Methods Childhood CKD was identified using ICD-9 codes in the population-based, Taiwan national health insurance research database between 1997 and 2011. Patients continuously receiving RASIs for ≥3 months without interruption > 30 days after CKD diagnosis were defined as incident users. Medication adherence was measured as the proportion of days covered (PDC) by RASI prescription refills during the study period. Multivariate logistic regression was employed to assess the odds for adherence (PDC ≥80%) to RASI refills. Results Of 1271 incident users of RASI chronic therapy, 16.9% (n = 215) had PDC ≥80%. Compared to the group with PDC < 80%, patients in the high adherence group more often had proteinuria (aOR [adjusted odds ratio]1.93; 95%CI [confidence interval], 1.18-3.17), anemia (aOR, 1.76; 95% CI, 1.20-2.58), and time to start of chronic use > 2 years (aOR, 1.12; 95%CI, 1.06-1.19). Odds of being non-adherent were increased by hypertension and older ages (comparing to < 4 years) at start of chronic use, 9-12 years (aOR, 0.38; 95%CI, 0.17-0.82), 13-17 years (aOR, 0.45; 95%CI, 0.22-0.93),≥18 years (aOR, 0.34; 95%CI 0.16-0.72) and males (aOR, 0.68; 95%CI, 0.49-0.94). Conclusions The rate of RASI prescription refilling adherence was relatively low and associated with CKD-specific comorbid conditions. This study identifies factors associated with low adherence and highlights the need to identify those who should be targeted for intervention to achieve better blood pressure control, preventing CKD progression.